Utilizing video laryngoscopy before thyroidectomy in a hospital in Mangalore - N., Manisha; Mathew, Ben S.; Amrita, (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
The highly debated opinion of whether a pre-operative video laryngoscopy was necessary to both patient care and doctor safety would be answered by the clinical insight into a local hospital who’s standard of care involves performing a video laryngoscopy before any major thyroid surgery. Aims and objectives of the study were to improve patient care and quality of life and ensure appropriate and proper investigation of the patient. Record based retrospective study assessing all patients that came for thyroidectomy during the time period from January 2022 to December 2022. 100% of patients who came to our hospital with any indication of thyroidectomy underwent video laryngoscopy preoperatively. We recommend video laryngoscopy (VLS) to be done in a 100% of cases of patients posted for thyroidectomies in the near future as it benefits both the patient and the doctor.